Chemical composition and fermentative losses of mixed sugarcane and pigeon pea silage - Pereira, Djalma Silva (2019)
Adding legumes to sugarcane silage is a strategy used to improve silage quality and reduce losses. This study’s objective was to evaluate the chemical composition and fermentation profile of silages sugarcane and pigeon pea. A completely randomized design was used, with five treatments and four replications. The treatments consisted of sugarcane silage with increasing pigeon pea proportions (0, 25, 50, 75 and 100%). The forages were ensiled in experimental microsilos that remained closed for 60 days. Their chemical compositions were evaluated by determining the pH value and dry matter, crude protein, neutral detergent fiber, acid detergent fiber, hemicellulose, cellulose and lignin content. Fermentation profiles were evaluated by determining the effluent, gas, and total dry matter losses and dry matter recovery of the silage. Including pigeon pea in sugarcane silage decreases the hemicellulose content and increases the crude protein, acid detergent fiber and lignin content. Fermentation losses are reduced by adding pigeon pea to sugarcane silage with reduced effluent and gas losses and increased dry matter.